Malaysian communications and multimedia commission’s powers in managing and regulating online publication - Shuaib, Farid Sufian (2012)

(untitled)
Malaysian Communications and Multimedia Commission (MCMC) is a body established under the Malaysian Communications and Multimedia Commission Act 1998, among others, to regulate all matters relating to communications and multimedia activities. Since it has a central role in regulating the internet, there is a need to examine the extent of power of the MCMC in regulating online publication. The power will be examined in respect of the policy objective of the Malaysian endeavour in riding the wave of information communication technology to leapfrog her economy through the Multimedia Super Corridor (MSC) and at the same time excluding online publication from censorship